2011
DOI: 10.1177/0148607110377096
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Feeding Tube Site and Respiratory Outcomes

Abstract: Background It is unclear if placing feeding tubes postpylorically to prevent respiratory complications is worth the extra effort. This study sought to determine the extent to which aspiration and pneumonia are associated with feeding site (controlling for the effects of severity of illness, degree of head-of-bed elevation, level of sedation, and use of gastric suction). Methods A retrospective analysis was performed on a large data set gathered prospectively to evaluate aspiration in critically ill, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…Previous studies have indicated that tube feeding leads to aspiration pneumonia (Metheny, 2006;Metheny, Stewart, & McClave, 2011). Most of our subjects were tube fed.…”
Section: The Journal Of Nursing Researchmentioning
confidence: 65%
“…Previous studies have indicated that tube feeding leads to aspiration pneumonia (Metheny, 2006;Metheny, Stewart, & McClave, 2011). Most of our subjects were tube fed.…”
Section: The Journal Of Nursing Researchmentioning
confidence: 65%
“…1 Gastric feedings are often tried first because they are easier to administer; however, they may be associated with increased risk for aspiration in some patients. 2 Therefore, monitoring for intolerance to feedings is a major nursing function. In this article, we report findings from a national survey of methods used by critical care nurses to assess tolerance to gastric tube feedings and discuss the findings in light of current enteral nutrition guidelines.…”
Section: Measuring Gastric Residual Volumesmentioning
confidence: 99%
“…It showed that the rates of pneumonia were significantly lower in patients receiving diet from the second portion of the duodenum on (19) .…”
Section: Enteric Position Of the Tubementioning
confidence: 99%